The Effectiveness Of Quranic Counseling To Reduce And Improve The Psychological Health Postpartum Mothers In Independent Midwife Practices - Suryati; Rosyad, Shelly Rodilah; Mariati, Nelly (Yayasan Rumah Ilmu Professor, 2026)
Quranic counseling is a counseling method applied to problem-solving using an approach based on the Quran. According to Erhamwilda, the fundamental teachings of Islam are the Quran and Hadith, which need to be explored critically to apply the basic counseling concepts contained therein professionally. This activity was conducted at the Hj. Saidatunnisa Pre-School of Postpartum Care (PMB Hj. Saidatunnisa), located in Banjarmasin City. The purpose of this activity was to determine the effectiveness of Quranic counseling in reducing and improving the psychological health of postpartum mothers. This study used a quantitative approach with a pre-experimental method with a one-group pretest-posttest design. The sample was drawn through purposive sampling, with 22 postpartum mothers. Data collection used a questionnaire on improving the psychological health of postpartum mothers. Data analysis involved grouping data based on sample variables, presenting data for each variable studied, and performing calculations to answer the research questions. The results showed that Quranic counseling was effective in reducing and improving the psychological health of postpartum mothers. Prior to Quranic counseling, many postpartum mothers experienced anxiety and mild depression related to their condition during childbirth. After undergoing Quranic counseling, all postpartum mothers felt calmer and were able to accept their own and their families' circumstances and were ready to face all possible eventualities.